Fałszerstwa dzieł sztuki – wybrane aspekty prawnokarne - Wojewoda, Ewelina; Truskolaska, Emilia (Studia Prawnoustrojowe, 2019)
With the practice of falsification works of art we are dealing for centuries. Basically since they just appeared. It is very difficult to determine the scale of this crime. These items are threatened by the phenomenon of counterfeiting due to the fact that they have not only the value of assets but also the non-pecuniary value: artistic, aesthetic and historical. Occurrence on the market of counterfeits is a serious threat fot the collectors and for a proper functioning art market. In the Polish legal system protection of works of art against falsification ensure the regulations contained in the Act of 6 June 1997. – Criminal Code and the Act of 23 July 2003. On the protection historic monuments and care of monuments. This paper presents a protection system of works of art in our country against the practice of falsification by analyzing the constituent elements of criminal offenses involving the forgery of works of art and turnover of fakes. The summary also highlights the imperfection of the current system and the lack of adequate protection of works of art which are not monuments.